Determining soil erosion rates on semi‐arid watersheds using radioisotope‐derived sedimentation chronology. Issue 6 (1st November 2016) - Polyakov, V. O.; Nichols, M. N.; Nearing, M. A.
Abstract: This study investigates erosion dynamics of the past 90 years in three small semi‐arid watersheds with histories of grazing and vegetation change. Activity of 137 Cs and excess 210 Pb from 18 cores collected from sedimentation ponds were measured using a gamma spectrometer. The sediment was dated using a constant rate of supply (CRS) model. This study represents the first time that reservoir sediment accumulation rates determined from fallout isotopes have been verified by direct volumetric measurements of aggradation based on topographic surveys. Measured sedimentation in the ponds ranged between 1.9 and 2.3 cm y −1, representing average sediment delivery rates from the watersheds of between 0.6 and 2.0 t ha −1 y −1 . These sediment delivery rates were in agreement with those established by other methods for similar catchments in the region. Past variations in sedimentation rates were identified and correlated with recorded history of anthropogenic disturbance. 137 Cs and 210 Pb methods are suitable for use in arid environments and can complement each other to increase reliability of erosion rate estimates. The abundance of stock ponds in southwestern USA presents an opportunity to quantify historic erosion and sediment transfer dynamics in areas that have not been well studied or instrumented. Published 2016. This article is a U.S. Government work and is in the public domain in the USA